The Effect of Teaching Strategies and Prior Knowledge on Students’ Achievement in Reading Comprehension - Debora Anggreini Sihite; Sumarsih Sumarsih; Didik Santoso (Universitas Negeri Medan, 2015)
The objectives of this experimental research were to find out whether: 1) students achievement in reading comprehension taught by using directed reading thinking activity (DRTA) strategy was higher than taught by using reciprocal teaching strategy. 2) Students’ achievement in reading comprehension with high prior knowledge was higher than that students with low prior knowledge, and 3) there was interaction between teaching strategies and prior knowledge on students’ achievement in reading comprehension. The population of this research was the students in grade VIII of SMP Dwi Tunggal T. Morawa in 2012/2013 school year. Prior knowledge test was conducted for classifying the students upon the high and low prior knowledge. Students’ achievement in reading comprehension was measured by using reading comprehension test. The data were analyzed by applying two-way analysis of variance (ANOVA) at the level of significant . Scheffe –test result also showed that high prior knowledge students got higher achievement if they were taught by using directed reading thinking activity strategy while low prior knowledge students got higher achievement if they were taught by using reciprocal teaching strategy. Keywords: Directed Reading Thinking Activity (DRTA) Strategy; Reciprocal Teaching Strategy; Achievement in Reading Comprehension; Prior Knowledge